2021
DOI: 10.1002/hep4.1645
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Coordinated Neutrophil Responses to the Human Fungal Pathogen, Candida albicans, in Patients With Cirrhosis

Abstract: Neutrophils are the most abundant white blood cell in the body and are key participants in the defense against fungal infections. Fungal infections occur often in patients with cirrhosis and are associated with increased 30‐day and 90‐day mortality. Previous studies have shown that specific neutrophil functions are abnormal in patients with cirrhosis, although the extent of neutrophil dysfunction is not well understood. We tested the ability of neutrophils from 21 hospitalized patients with cirrhosis and 23 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Here, the swarming assay was leveraged to dissect the abilities of circulating neutrophils to mobilize and contain C. albicans growth where healthy neutrophils swarmed and effectively restricted fungal growth while cirrhotic patient neutrophils failed to contain C. albicans. In contrast, neutrophils from transplant patients displayed more heterogeneity between patients in the ability of their swarms to restrict fungi [30,31]. We found that human disease alters the whole population of circulating neutrophils independent of disease severity; however, one limitation of the assay is the difficulty in parsing out individual neutrophils to follow their response to the target over time.…”
Section: Discrete Functional and Phenotypic Neutrophil Characteristics In Response To Fungal Infectionmentioning
confidence: 83%
See 1 more Smart Citation
“…Here, the swarming assay was leveraged to dissect the abilities of circulating neutrophils to mobilize and contain C. albicans growth where healthy neutrophils swarmed and effectively restricted fungal growth while cirrhotic patient neutrophils failed to contain C. albicans. In contrast, neutrophils from transplant patients displayed more heterogeneity between patients in the ability of their swarms to restrict fungi [30,31]. We found that human disease alters the whole population of circulating neutrophils independent of disease severity; however, one limitation of the assay is the difficulty in parsing out individual neutrophils to follow their response to the target over time.…”
Section: Discrete Functional and Phenotypic Neutrophil Characteristics In Response To Fungal Infectionmentioning
confidence: 83%
“…These patient-based data are promising as these suggest that specific numbers of granulocyte subpopulations lead to improved immune-based therapies. Given evidence of specific human neutrophil subpopulations [30,31], these data suggest that the higher dose is effective because either patients require a large number of granulocytes overall or the higher dose may have contained a degree of specific neutrophil subpopulations.…”
Section: Therapeutic Potential For Patients With Fungal Disease and Perspectivesmentioning
confidence: 97%
“…To confirm the purity of neutrophils at the end of the isolation process, WrightGiemsa staining (Thermo Fisher Scientific) was performed as previously reported and viabilities were verified via live/dead staining with acridine orange/propidium iodine staining and counting on the LUNA automated fluorescent cell counter at a 1:10 dilution. Both were reported at or above 87% (31,32).…”
Section: Primary Human Neutrophilsmentioning
confidence: 99%
“…This defect may be due to neutrophil exhaustion in the setting of persistently elevated circulating levels of inflammatory cytokines. 56 Patients with sAH present a more markedly reduced neutrophil antimicrobial activity, including phagocytosis and oxidative burst. 21 This underlying immune dysfunction in patients with AH may explain the lack of neutrophil functioning, thus increased prevalence of candidemia.…”
Section: Fungal Pathogensmentioning
confidence: 99%